Level and determinants of pentavalent vaccine dropout during infancy: A hierarchical analysis of community-level longitudinal study - Tariku Tesfaye Bekuma; Assefa Seme; Saifuddin Ahmed; Muluemebet Abera (PLoS ONE, 2025)
Background An estimated 23 million children under the age of one do not get the recommended basic vaccinations globally, and Ethiopia is one of the 10 countries where almost 60% of these children live. The alarming decline in childhood vaccination is leaving millions of children at risk of devastating but preventable diseases. Vaccination dropout poses a significant challenge in ensuring that children receive the full protection provided by vaccines. In Ethiopia, individual vaccine coverage has improved, but the proportion of fully vaccinated children with all recommended vaccines remains low. The study aimed to examine the level and determinants of pentavalent vaccine dropouts during infancy. Methods The study utilized data from the PMA Ethiopia panel survey, which was conducted in three regions: Amhara, Oromia, and the former SNNP. A multi-stage cluster design with urban-rural stratification was used to draw a probability sample of households and women of reproductive age. We employed a multilevel logistic regression analysis in light of the hierarchically clustered nature of PMA data and the results are reported in odds ratio. The measures of variation were explained by intra-cluster correlation, median odds ratio, and proportional change in variance. Results A total of 1295 infants were included in the final analysis. The result shows that a dropout from the first to the third dose of pentavalent was 37.48%. Pentavalent dropout rates were about two times (AOR = 1.84, 95% CI: 1.24–2.72) higher for infants born at home than for babies born at a health facility, and two times (AOR = 1.77, 95% CI: 1.04 2.99) higher for infants born to mothers who perceived the community did not support postnatal care than for babies born to mothers who believed the community supported it. Infants whose mothers had trouble accessing PNC following the COVID-19 pandemic were dropped out of Pentavalent five times higher (AOR = 5.06, 95% CI: 1.32–19.48). Pentavalent dropout is more than three times (AOR = 3.78, 95% CI: 1.75–8.16) higher among those who lived in the former SNNP region and more than two times (AOR = 2.75, 95% CI: 1.17–6.43) higher among infants born to mothers who lived in a community with a high level of poverty. Conclusion and recommendation The dropout rate from the first to the third pentavalent vaccine is higher than what has been reported in other studies in Ethiopia and abroad. Residing in a high-poverty community, giving birth at home, perceiving that the community did not support postnatal care, and having trouble accessing PNC following COVID 19 significantly determined pentavalent dropout. Improving health education, healthcare access, institutional delivery, and the health systems linkage are therefore essential to addressing these problems in the targeted population.